2016
DOI: 10.3892/etm.2016.3276
|View full text |Cite
|
Sign up to set email alerts
|

Long-term expression of zinc transporters in hippocampus following penicillin-induced developmental seizures and its regulation by E-64d

Abstract: Autophagy has been shown to be involved in the pathophysiology of developmental seizure-induced brain damage. The present study aimed to examine whether E-64d, an autophagy inhibitor, was able to facilitate developmental seizure-induced hippocampal mossy fiber sprouting, in particular sprouting-associated zinc transporter signals. Recurrent seizures were induced by penicillin every other day in Sprague-Dawley rats from postnatal day 21 (P21). Rats were randomly assigned into the control group (CONT), recurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Our results indicated that E-64d protected HT22 cells against glutamate-induced injury. To evaluate the effects of E-64d on neuronal cells, we first established an in vitro model by exposing HT22 cells and primary mouse astrocytes to 15 mM glutamate for 24 h. Our findings are consistent with our previous work, suggesting that E-64d exerts a neuroprotective effect against epilepsy-induced neuronal damage [ 41 , 62 ]. Using this glutamate-induced injury model, we then investigated the mechanisms by which E-64d exerts protective effects.…”
Section: Discussionsupporting
confidence: 88%
“…Our results indicated that E-64d protected HT22 cells against glutamate-induced injury. To evaluate the effects of E-64d on neuronal cells, we first established an in vitro model by exposing HT22 cells and primary mouse astrocytes to 15 mM glutamate for 24 h. Our findings are consistent with our previous work, suggesting that E-64d exerts a neuroprotective effect against epilepsy-induced neuronal damage [ 41 , 62 ]. Using this glutamate-induced injury model, we then investigated the mechanisms by which E-64d exerts protective effects.…”
Section: Discussionsupporting
confidence: 88%
“…This contradiction may be related to the different types and quantities of Zn transporters, differences in Zn accumulation in cells, and external stimulation; Zn oxide nanoparticles can also increase the activity of lysosomal proteases in skin cells to activate autophagy flux (Rudolf & Rudolf, 2017). In contrast, Zn accumulation in the lysosomes of dopamine neurons has little effect on autophagy flux or acid protease expression (Ni et al, 2016). In mussels, in addition to increasing the activity of lysosomal proteases, Zn nanoparticles disrupt membrane stability, releasing large quantities of proteases into the cytoplasm, thus blocking later stages of autophagy (Falfushynska et al, 2019).…”
Section: Effects Of Transition Metals On Autophagymentioning
confidence: 99%
“…Dedicator of cytokinesis protein 7 (DOCK7), which is localized to the developing axons, activates Rac1 and Rac3 small GTPases and regulates neuronal polarity; moreover, its variants cause developmental and epileptic encephalopathy 23 (DEE23) (63,64). SLC39A7 (ZIP-7) is a Zn 2+ efflux transporter in the ER membrane; ZIP7 depletion causes neurodevelopmental impairments and ZIP7 signaling pathway provides neuroprotective effects in recurrent seizures (65,66).…”
Section: Discussionmentioning
confidence: 99%